Freedom of Information Legislation in Australia: A Review - Allars, Margaret (Revue internationale des Gouvernements Ouverts, 2017)
Freedom of information legislation was introduced at the federal level in Australia in enactment of the Freedom of Information Act 1982 (“FOI Act”). Within the decade that followed, freedom of information legislation was introduced in each State and Territory in Australia, substantially based on the original model of the federal FOI Act.[if !supportFootnotes]. The federal and New South Wales (“NSW”) legislation underwent substantial changes in 2009 to 2010. In May 2013, the federal Attorney-General announced that Australia had joined the Open Government Partnership (“OGP”). After a change of government, Australia’s commitment to the OGP was not progressed. In November 2015 after a change of Prime Minister, the new Prime Minister stated that Australia remained committed to the OGP. However, Australia failed to provide a national action plan for three plan cycles, from 2014 to 2016.